Implementace systému řízení kvality v univerzitních laboratořích - Mahajan, Rohit (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2023)
An organization uses a Quality Management System (QMS) to meet its quality objectives and policies through a set of processes and procedures. Quality Management systems are mainly used in industries to improve product quality and meet customers’ requirements. Implementing a quality management system in the education sector is challenging and less common and measurement of performance is more focused on teaching methods and several publications; also, university test laboratories are used for teaching and research activities. Another reason is educational institutions often face resource constraints, including limited budgets, time, and personnel. This project is about implementing a quality management system in the laboratory of Brno University of Technology. The objective of study is to understand the current situation, identify critical nonconformities, and provide suggestions for their elimination, which will assist the laboratory team in implementing a quality management system. The author conducted an internal audit to assess the current state of the laboratory and identify any gaps. The author used ISO/IEC 17025-2017 standards for analysis of gap. As a result, the author identified laboratory comply with 44% requirements and in 31% areas need to be improvements, such as equipment handling procedures, maintenance plans for equipment, strategies for handling and maintaining missing records, and the absence of implemented sampling methods, internal audit, and management review procedures. The author shared significant findings with the laboratory team and suggested improvements. The author suggested making procedures for handling the equipment, making a maintenance plan, and documenting the sampling method. During the discussion, the author explained the limitations that hindered the effective analysis of the study and the reasons behind them. In the last, the author provided recommendations for future work.

An organization uses a Quality Management System (QMS) to meet its quality objectives and policies through a set of processes and procedures. Quality Management systems are mainly used in industries to improve product quality and meet customers’ requirements. Implementing a quality management system in the education sector is challenging and less common and measurement of performance is more focused on teaching methods and several publications; also, university test laboratories are used for teaching and research activities. Another reason is educational institutions often face resource constraints, including limited budgets, time, and personnel. This project is about implementing a quality management system in the laboratory of Brno University of Technology. The objective of study is to understand the current situation, identify critical nonconformities, and provide suggestions for their elimination, which will assist the laboratory team in implementing a quality management system. The author conducted an internal audit to assess the current state of the laboratory and identify any gaps. The author used ISO/IEC 17025-2017 standards for analysis of gap. As a result, the author identified laboratory comply with 44% requirements and in 31% areas need to be improvements, such as equipment handling procedures, maintenance plans for equipment, strategies for handling and maintaining missing records, and the absence of implemented sampling methods, internal audit, and management review procedures. The author shared significant findings with the laboratory team and suggested improvements. The author suggested making procedures for handling the equipment, making a maintenance plan, and documenting the sampling method. During the discussion, the author explained the limitations that hindered the effective analysis of the study and the reasons behind them. In the last, the author provided recommendations for future work.
Implementation of Quality Management System in University Laboratories
Keywords: Quality management system; ISO/IEC 17025:2005 standards; Test laboratory; Internal Audit.; Quality management system; ISO/IEC 17025:2005 standards; Test laboratory; Internal Audit.